HISTOLOGICAL RESEARCH OF RAT’S KIDNEY IN A NORM AND ІN EARLY TERMS OF STREPTOZOCINE-INDUCED DIABETES MELLITUS - Pokotilo, P.B. (World of Medicine and Biology, 2012)
Organization of the components creating filtrational barrier rat’s kidney and arteries conditions on 42 days of the experimental streptozotocinindactional nephropathy was investigated. The obtained data allow to perform comparative characteristics of morphological changes of the filtrational barrier components and arteries of rat’s kidney in the pathing dynamics of the experimental streptozotocinindactional nephropathy.